Implementation of Social Inquiry Learning Model to Improve Social Problem Solving Skills in Elementary School Students - Sumarsih Sumarsih (Universitas Tanjungpura, 2021)
This study aims to determine: (1) Social problem-solving skills before applying the social inquiry learning model to fifth-grade students of SDN (Public Elementary School) 13 Sungai Ambawang. (2) Social problem-solving skills after applying the social inquiry learning model to the fifth-grade students of SDN 13 Sungai Ambawang. (3) The improvement of social problem-solving skills after applying the social inquiry learning model to the fifth-grade students of SDN 13 Sungai Ambawang. This type of research is action research conducted in fifth grade SDN 13 Sungai Ambawang. The study results showed that: (1) Social problem-solving skills prior to the implementation of the social inquiry learning model in fifth-grade students of SDN 13 Sungai Ambawang were in low qualification. (2) Social problem-solving skills after implementing the social inquiry learning model for fifth-grade students of SDN 13 Sungai Ambawang in the first cycle entered moderate qualifications, and the implementation of the second cycle entered high qualifications. (3) There is an increase in social problem-solving skills after applying the social inquiry learning model to the fifth-grade students of SDN 13 Sungai Ambawang.